(untitled) (Economic and Political Thought, 2016)
The aim of the paper is to elaborate the current state of accidents at work in Poland in the years 2002–2014. The emphasis is placed on the analysis of the level, structure and trends in accidents at work in Poland. In the article also causes and effects of the occupational accidents are discussed. The article consists of 4 main parts: introduction, information in the field of registration of accidents at work – European and national context, occupational accidents in numbers and conclusions. The main source of empirical data were statistics provided by the Central Statistical Office in Poland. The Author has proven that in the considered time period working conditions in relation to the accidents at work did not improve significantly. Work in Poland did not become safer. In the years 2002–2014 the total number of occupational accidents and the overall ratio of accidents at work (the number of the injured persons per 1,000 of the employed) did not change a lot.